На ветрах времени: размышления о книгах / Владимир Акимов - Акимов Владимир Михайлович (Детская литература, 1991)
Экземпляры: ф31 (20210311) / Инвентарный номер: 1995 / Цена: 2.70 / Сис.шифр: 83.3(2Рос=Рус)ст / Авт.знак: А 39 / ГРНТИ: 17 / ББК: 83.3(2Рос=Рус)ст